Faktor-Faktor yang Mempengaruhi Minat Menggunakan Layanan Financial Technology Peer To Peer Lending Syariah - Hasibuan, Henny Triyana (E-Jurnal Akuntansi, 2021)
The purpose of this study was to see the factors that influence the interest of users of Islamic peer to peer lending services using the Unified Theory Of Acceptance and Use Of Technology 2 (UTAUT2) model. The exogenous variables in this study are performance expectancy, effort expectancy, social influence, facilitating conditions, price value, hedonic motivation and habit, while the endogenous variable is behavior intention. The data was collected by distributing questionnaires using google forms. The data analysis technique used is Structural Equational Modeling (SEM). The results showed that the variables of performance expectancy, social influence, hedonic motivation and habit had no effect on behavior intention to use Islamic peer to peer landing fintech services, while the variables Effort Expectancy, Facilitating Condition and Price Value had a positive effect on behavior intention using Islamic peer to peer lending services. Keywords: UTAUT2; Behavior Intention; Financial  Peer To Peer Islamic Lending; SEM.